Significantly enhanced recovery of acute liver failure by liver targeted delivery of stem cells via heparin functionalization. (July 2019) - Hwang, Youngmin; Kim, Jong Chul; Tae, Giyoong
Abstract: Acute liver failure (ALF) occurs by insufficient detoxification of toxic materials in the liver, generating excess reactive oxygen species (ROS). Mesenchymal stem cell (MSC) therapy can be a promising approach for the treatment of liver diseases including ALF by anti-inflammatory activity and secretion of cytokines associated with tissue regeneration. However, the efficacy of MSC therapy is generally poor, mainly due to a low survival and engraftment of administered cells. In this study, we demonstrated that the enhanced delivery of human adipose-derived stem cells (hADSCs) to the damaged liver by the coating of lipid-conjugated heparin could result in significantly improved recovery from ALF in a mouse model. First, the therapeutic effect of secretomes of hADSCs on acetaminophen (APAP)-induced hepatic cell damage was confirmed regardless of the coating of lipid-conjugated heparin on hADSCs in vitro . Then, the therapeutic effects of lipid-conjugated heparin coated hADSCs (Lip-Hep/hADSC group) were analyzed compared to hADSCs themselves (hADSC group) using an APAP-induced ALF model in vivo . Intravenous administration of hADSCs could lower the elevated serum levels of aspartate transaminase (AST) and alanine transaminase (ALT), but Lip-Hep/hADSC group showed faster decrease in serum levels of AST and ALT to the normal values compared to hADSC group. Enhanced delivery and longer retention of hADSCs in the damage liver by the coating of lipid-conjugated heparin were confirmed by optical imaging of isolated organs using labeled cells and immunofluorescence staining of liver tissue sections against human nuclei. A significantly increased level of human hepatic growth factor (hHGF), a representative secretome from hADSC, significantly reduced levels of macrophage and CYP2E1, implying alleviated inflammatory response, were detected by immunofluorescence staining from Lip-Hep/hADSC group compared to hADSC group. These results well coincided with the improved recovery of the damaged liver from Lip-Hep/hADSC group than hADSC group in histological analysis. Thus, the coating of lipid-conjugated heparin on hADSCs has a great potential to improve the therapeutic effect of cells on the liver injury.